Photostable Ratiometric Pdot Probe for in Vitro and in Vivo Imaging of Hypochlorous Acid - Wu, Li; Wu, I-Che; DuFort, Christopher C; Carlson, Markus A; Wu, Xu; Chen, Lei; Kuo, Chun-Ting; Qin, Yuling; Yu, Jiangbo; Hingorani, Sunil R; Chiu, Daniel T (Journal of the American Chemical Society, 2017)
Developing probes for the detection of reactive oxygen species (ROS), a hallmark of many pathophysiological process, is imperative to both understanding the precise roles of ROS in many life-threatening diseases and optimizing therapeutic interventions. We herein report an all-in-one fluorescent semiconducting polymer based far-red to near-infrared (NIR) Pdot nanoprobe for the ratiometric detection of hypochlorous acid (HOCl). The fabrication takes the advantage of flexible polymer design by incorporating target-sensitive and target-inert fluorophores into a single conjugated polymer to avoid leakage or differential photobleaching problems existed in other nanoprobes. The obtained nanoprobe has improved performance in HOCl sensing, such as high brightness, ideal far-red to NIR optical window, excellent photostability, self-referenced ratiometric response, fast response, and high selectivity. The dual-emission property allows the sensitive imaging of HOCl fluctuations produced in living macrophage cells and peritonitis of living mice with high contrast. This study not only provides a powerful and promising nanoprobe to be potentially used in the investigations of in situ HOCl status of diseases in living systems but also puts forward the design strategy of a new category of ratiometric fluorescent probes facilitating precise and reliable measurement in biological systems.